(untitled) - Mauricio Rocha Calomeni; José Antonio Martins da Silva Rocha; Alair Pedro Ribeiro da Silva; Luiz Henrique Brandão Ribeiro; Luciene Marques; Maria Auxiliadora Freire Siza; Vernon Furtado da Silva (Arquivos de Neuro-Psiquiatria)
According to World Health Organization, approximately 15 million people are affected by cerebrovascular accident in the world. We study the effect of brain stimulation plus an imaging procedure used as biofeedback training for recovery of motor functions impaired by CVA. Four individuals aged between 33 and 72 years were included in the study, of both genders, with hemiparesis on the left arm due to the CVA. They had their brain activity monitored by EEG. Functional tasks were evaluated according to an observational model proposed by the international classification of functioning and by runtime. The training was composed of 12 sessions of 30 minutes of stimulation by light and sound, as well as imaging procedures. Results revealed that improvements in the performance of the task, with regard to both the runtime and the functional quality of movements, are more related to the increase of effectiveness of neuronal function. Segundo a Organização Mundial da Saúde, aproximadamente 15 milhões de pessoas no mundo sofrem acidente vascular cerebral (AVC). Estudaram-se os efeitos da estimulação cerebral associada à imagética, como treinamento de biofeedback, para a recuperação das funções motoras deterioradas pelo AVC. Foram incluidos 4 indivíduos com idade entre 33 e 72 anos, de ambos os gêneros, e com hemiparesia no braço esquerdo devido ao AVC. Esses pacientes tiveram a atividade cerebral monitorada por EEG. A tarefa funcional foi avaliada de acordo com o modelo de observação proposto pela Classificação Internacional de Funcionalidade e pelo tempo de execução. O treinamento consistiu de 12 sessões de 30 minutos de estimulação por luz e som associado à imagética. Os resultados revelaram melhoria no desempenho da tarefa, tanto em relação ao tempo de execução quanto à qualidade funcional do movimento, e que está mais relacionada com o incremento de eficácia da função neuronal.